1978
DOI: 10.1139/z78-320
|View full text |Cite
|
Sign up to set email alerts
|

Development of longitudinal mucosal folds in the intestine of the anadromous sea lamprey, Petromyzon marinus L., during metamorphosis

Abstract: During metamorphosis of the anadromous sea lamprey, Petromyzon marinus L., the larval intestine develops numerous longitudinal folds. The initiation of this event is marked by a decrease in diameter of the intestine and in the height of the typhlosole and is followed by an increase in numbers of cells undergoing DNA synthesis, first in the anterior intestine and later in the posterior intestine. Foci of proliferating cells along the epithelial walls of both regions result in the development of longitudinal fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Excluding typhlosole with high mucosal folds for the most part, L. japonicum in the present study revealed the regular pattern of arrangement in the three types of mucosal folds in opposition to some parasitic species previously reported, e.g. Petromyzon marinus, which have no definite pattern of arrangement (Youson and Connelly, 1978;Hilliard et al, 1983), indicating the difference of developing patterns in mucosal folds among species. Mucosal folds appear to have resulted from an elevation of both the epithelium and the underlying connective tissue and muscle, which have commenced after metamorphosis stage 4 in parasitic P. marinus (Youson and Connelly, 1978).…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Excluding typhlosole with high mucosal folds for the most part, L. japonicum in the present study revealed the regular pattern of arrangement in the three types of mucosal folds in opposition to some parasitic species previously reported, e.g. Petromyzon marinus, which have no definite pattern of arrangement (Youson and Connelly, 1978;Hilliard et al, 1983), indicating the difference of developing patterns in mucosal folds among species. Mucosal folds appear to have resulted from an elevation of both the epithelium and the underlying connective tissue and muscle, which have commenced after metamorphosis stage 4 in parasitic P. marinus (Youson and Connelly, 1978).…”
Section: Discussioncontrasting
confidence: 77%
“…Apical pits, which indicate the existence of secretory cells releasing the content of the granules, have been reported from only feeding stage of parasitic species, with an example of P. marinus (Youson, 1981). These characteristics indicate increase of nutrient absorption which enables more rapid growth during the parasitic period, as already reported for P. marinus (Youson and Connelly, 1978;Youson, 1981).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations